A morphological model for the solvent-enhanced conductivity of PEDOT:PSS thin films - Mantovani Nardes, Alexandre; Janssen, René A. J.; Kemerink, Martijn (Advanced functional materials, 2008)
The well-known enhanced conductivity of poly(3,4-ethylenedioxythiophene):poly(4-styrenesulfonate) (PEDOT:PSS) thin films that is obtained by addition of high-boiling solvents like sorbitol to the aqueous dispersion used for film deposition is shown to be associated with a rearrangement of PEDOT-rich clusters into elongated domains, as evidenced from STM and AFM. Consistently, temperature dependent conductivity measurements for sorbitol-treated films reveal that charge transport occurs via quasi 1D variable range hopping (VRH), in contrast to 3D VRH for untreated PEDOT:PSS films. The typical hopping distance of 60-90 nm, extracted from the conductivity measurements is consistent with hopping between the 30-40 nm sized grains observed with scanning probe microscopy.
Gesehen am 16.12.2019